(untitled) (Sociologisk Forskning, 2002)
Entrepreneurship as existential act In this paper I argue that business economics tends to present an overrationalized view of entrepreneurial action. Entrepreneurship is basically an existential type of action, as it includes elements of tradition-breaking activities and emotions related to coping with uncertainty. These existential aspects are best revealed as one studies aspects of entrepreneurship that have been marginalized in entrepreneurial studies, such as first time entrepreneurs, women entrepreneurs, ethnic entrepreneurship, entrepreneurs with an academic background and entrepreneurship in undersocialized industrial populations. The existential aspects of entrepreneurship are only partially taken into account by the new economic sociology, emphasizing the value of socializing for it own sake. More generally a focus upon the existential aspects of entrepreneurial action challenges the classical sociological views of order and individuality, pointing to a neo-classical view of modernity which puts uncertainty in the center of modernity as well as recognizing its unmistakingly romantic traits.